DIVERSIDADE DE INVERTEBRADOS ASSOCIADOS À SERAPILHEIRA - MEIRA, Vandressa Raquel Lucas Poloni; SOUZA, Bianca de Oliveira; SILVA, Elicleia Maria de Souza; BRASIL, Joice Kely Vasconcelos; GUIMARÃES, Leticia Soares; VARGAS, Elizangela Leite (ANAIS DO ENIC, 2017)
-